Strategies for promoting Gender and Social Inclusion (GESI) in the agribusiness sector in Zambia: experiences from the field - Greehy, P.; Enokenwa Baa, Ojongetakah; Nortje, Karen (International Water Management Institute (IWMI), 2023)
Building on the Reclaim Sustainability! (RS!) programme’s baseline studies and the Gender and Social Inclusion (GESI) Reports, and in partnership with CGIAR Initiative on Diversification in East and Southern Africa (Ukama Ustawi) through International Water Management Institute (IWMI), Solidaridad facilitated commodity specific voice amplification dialogues in Zambia focused on cotton and fruits and vegetables farmers. These GESI engagements were designed to form the basis for future programs around voice amplification, gender and social inclusion across agri-business value chains, policy, advocacy, and innovation acceleration The commodity specific dialogues used a co-design approach in order to construct end-user archetypes of typical audiences for program engagement. Over a two week period between November and December 2022, Solidaridad’s commodity teams, supported by the Network’s Gender Expert, visited cotton and fruits and vegetable farmers across Zambia in the following districts: Lusaka, Chongwe, Mazabuka, Chibombo, Kabwe,Mumbwa, Choma , Magoyi, Nyimba , Petauke and Katete. In groups of not more than 15 per community, the team engaged in dialogue with women (60), youth (3) and men (30) farmers, commodity relevant key informants, individuals in influential spaces and interest groups across the Cotton and Fruits and Vegetables value chains. This included government officials, market players such as Freshmark (Shoprite), Good nature Agro, Agricultural input aggregators, industry union representatives, policy makers, district agricultural officers, and most importantly, women smallholder farmers.